Degradabilidade ruminal de diferentes gramíneas do gênero Cynodon spp. em quatro idades de corte - Monção, Flávio P. [UNESP]; De Oliveira, Euclides R.; De Gabriel, Andréa M.A.; De Souza, Rayanne; Moura, Lais V.; Lempp, Beatriz; Dos Santos, Mariana V. (Revista Brasileira de Ciencias Agrarias, 2014)
The objective of this study was to evaluate the ruminal degradability of dry matter of five grasses (Tifton 85, Jiggs, Russel, Tifton 68 and Vaquero) belonging to the genus Cynodon spp. at four ages of regrowth (28; 48; 63 and 79 days), by in situ technique. We used three steers of the Holstein/jersey race, neutered, with 40 months of age and approximate weight of 450 kg, rumen cannulated. The samples were incubated in the rumen in descending order in the time of 96, 48, 36, 12, 6 and 0 hours. The Tifton 68 and Tifton 85 presented best levels of fraction a, b potential and effective degradability of dry matter of cutting interval of 79 days differed from other genotypes. Russell genotype showed lower levels of effective degradability (25.51%) and highest content of nondegradable fraction (52.69%) of dry matter of cutting interval of 79 days and should be managed at a lower age of cutting. Up to 79 days, the genotypes Tifton, Tifton 85 and 68 were the ones which presented best levels of potential and effective degradability of dry matter. All the genotypes can be managed up to 28 days of regrowth.
Ruminal degradability of different grasses of the genus Cynodon spp. at four cutting ages
Keywords: Forage; In situ kinetics; Jigs; Russel; Tifton